Meal replacements, reduced energy density eating and weight loss maintenance in primary care patients: A randomized controlled trial - Lowe, Michael R. (2013)
OBJECTIVE: To compare the presence or absence of meal replacements (MRs) and an energy density (ED) intervention to facilitate weight loss maintenance. DESIGN AND METHODS: 238 overweight primary care patients (mean BMI= 39.5 kg/m(2)) began the study; 132 completed the 12-week weight loss phase. Participants were randomly assigned to one of four maintenance conditions formed by crossing the presence or absence of MRs (MR+/MR−) and of the ED program (ED+/ED−) during a subsequent 9-month maintenance phase. Follow-ups assessments occurred 1 and 2 years after treatment termination. RESULTS: Participants initially lost 6.1 kg. Analyses of variance based on weight change from the beginning of the maintenance phase to the 2-year follow-up produced a significant interaction. All groups except ED+/MR− regained substantial weight during follow-up; the ED+/MR− group regained significantly less weight than the control group at both follow-up assessments. No significant effects of treatment were found for several variables that were expected to mediate these outcomes. CONCLUSIONS: Because weight losses achieved in lifestyle change programs for obesity are rarely maintained, the superior outcome achieved by the ED+/MR− condition is notable. Nonetheless, methodological issues and inability to identify a potential mediator of this outcome makes replication of this finding essential.